Preliminary studies on microbial and physico-chemical processes on compost / Margaret Chan Kit Yok ... [et al.]. - Chan Kit Yok, Margaret; Gee Moi, Liew; Heng Yen, Kong; Khalid, Khadijah (2005)
The preliminary studies of the microbial dynamic and population of the composting process of ornamental palm leaf waste showed that the physico-chemical factors of the compost process played a vital role. The three phases of composting: the degradation phase, the conversion phase and maturation phase were indicated by temperature and pH pattern throughout the composting process of the palm leaves over a period pf 100 days. The temperature pattern showed a lower range of a classical decomposing process, rising from an initial 28 0C to 32õ C at the mesophilic stage and ranging 40 0 C to 43 0 C at the thermophilic stage before tapering to below 40 0 C. The pH experienced a slight drop from 6.8 to 6.7 before increasing to 7.1. The turning frequency and the shredding of the raw materials had accelerated the microbial activity.